2015
DOI: 10.1017/s0033291715001361
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of cortical structures in adolescent-onset conduct disorder

Abstract: The present study indicates that AO-CD is characterized by cortical structural abnormalities in the paralimbic system, and, in particular, we highlight the potential role of deficient structures including the precuneus and PCC in the etiology of AO-CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 76 publications
(127 reference statements)
4
17
1
Order By: Relevance
“…Our results support previous studies showing associations between CD and alterations in cortical thickness (CT), surface area (SA), and local gyrification index (lGI). As hypothesized, and as previously found in predominantly male samples, [28][29][30][31][32] CD was associated with lower ventromedial prefrontal cortex (vmPFC) CT. This was accompanied by higher gyrification in overlapping regions of vmPFC, as well as the posterior insula, in the CD group.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our results support previous studies showing associations between CD and alterations in cortical thickness (CT), surface area (SA), and local gyrification index (lGI). As hypothesized, and as previously found in predominantly male samples, [28][29][30][31][32] CD was associated with lower ventromedial prefrontal cortex (vmPFC) CT. This was accompanied by higher gyrification in overlapping regions of vmPFC, as well as the posterior insula, in the CD group.…”
Section: Discussionsupporting
confidence: 70%
“…These studies have reported lower CT in the prefrontal cortex (PFC), [28][29][30][31] superior temporal cortex, [28][29][30][31][32] supramarginal/angular gyrus, 29,32,33 precuneus, 28,29,31,32 and fusiform gyrus, 29,32 and lower SA in PFC 29,33 in participants with CD compared to controls. Furthermore, lower gyrification in the OFC/vmPFC, 32 and higher gyrification in the superior frontal gyrus (SFG), insula, fusiform gyrus, 30 and precentral gyrus 32 have been reported in individuals with CD versus controls. Despite considerable overlap between the regions that have been identified using SBM and VBM methods, SBM studies have highlighted additional regions that have not yet been incorporated in neurodevelopmental models of CD.…”
mentioning
confidence: 99%
“…It presents repetitive and chronic aggressive and antisocial behavior in which the basic rights of others or major age appropriate norms or rules of society are violated (APA, 2000). CD has been reported to occur in about 16% of preadolescents (Olsson, 2009; Jiang et al, 2015; Zhang et al, 2015), and may co-exist with other disorders, such as attention-deficit/hyperactivity disorder (ADHD) (Rubia, 2011), oppositional-defiant disorder (Loeber et al, 2000), and substance abuse (Whitmore et al, 1997). Aggressive and antisocial behavior displayed by children with CD might reflect atypical empathic responses to others' suffering (Blair, 2005), several behavioral studies have reported findings suggesting that CD youth may be deficient in empathy (Cohen and Strayer, 1996; Blair et al, 2001; Blair, 2005; Wied et al, 2005; Schwenck et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, several network hubs observed in HCs, such as bilateral insula and the right superior temporal cortex, which showed significant group differences in betweenness, were essentially absent from the CD network. Given that selective damage in the superior temporal cortex and insula have been observed repeatedly in several CD cohorts91050, the absence of such cortical hubs in CD may explain why certain brain regions show disproportionately high levels of connection and, as a result, preferential vulnerability to CD pathology. Since brain hubs tend to have more metabolically costly functional connections, they are likely to be more susceptible to disorders47.Thus, the alteration of such hubs may lead to deficient information flow and the domain of impairments characteristic of CD, such as empathy and perception of others’ feelings5152.…”
Section: Discussionmentioning
confidence: 99%
“…CD has been associated with genetic vulnerability, low-level physical arousal, and electrophysiological changes during feedback processing234 in previous researches. Neuroimaging studies have also described aberrations in brain structure and function, including prefrontal, temporal, and parietal cortical regions as well as subcortical structures, in people diagnosed with CD5678910. Most of the regions identified as having aberrations overlapped with so-called brain “hubs” in graph theory11, including orbitofrontal cortex, anterior cingulate cortex, insular cortex, and superior temporal cortex.…”
mentioning
confidence: 99%